A Bioguided Approach for the Screening of Antibacterial Compounds Isolated From the Hydroalcoholic Extract of the Native Brazilian Bee’s Propolis Using Mollicutes as a Model - Hochheim, Sabrina; Pacassa Borges, Pamela; Boeder, Ariela Maína; Scharf, Dilamara Riva; Simionatto, Edésio Luiz; Yamanaka, Celina Noriko; Alberton, Michele D.; Guedes, Alessandro; de Cordova, Caio Mauricio Mendes (Frontiers in Microbiology, 2020)
Nature is a vast source of medicinal substances, including propolis, which has been extensively investigated. Propolis is a resinous substance produced by bees from the exudates of plants that they collect and modify in their jaws; it is a rich and complex matrix with secondary metabolites of diverse botanical origins. The objective of this study was to apply an in vitro bioguided approach using as a model system the mollicutes with a sample of propolis from the Brazilian native bee Melipona quadrifasciata (mandaçaia) in order to identify potential new molecules with antimicrobial activity. A crude hydroalcoholic extract was obtained and submitted to liquid-liquid partitioning with solvents of different polarities, generating four different fractions: aqueous, dichloromethane, butanol, and ethyl acetate fractions. The antimollicute activity assays served as a basis for the bioguided fractionation. The dichloromethane fraction was the most promising, exhibiting a minimal inhibitory concentration (MIC) of 125 μg/mL against Mycoplasma pneumoniae. After purification by column liquid chromatography, a subfraction presenting MIC of 15.6 μg/mL against Mycoplasma genitalium was highlighted. The fractions were also tested against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Using gas chromatography coupled to a mass spectrometer (GC-MS), several volatile compounds were identified in the nonpolar fractions of this propolis. However, the more purified molecules had no better antimollicute activity than their original subfraction. Apparently, the synergism among its compounds is largely responsible for the antibacterial activity of the propolis of this native Brazilian bee.